Hidden properties of city plans: A case study of Łódź - Lamprecht, Mariusz (European Spatial Research and Policy, 2020)
The article analyses the transformations and the internal diversity of the oldest urban structures of central Łódź, one of the biggest Polish cities. 19th-century Łódź was one of the greatest centres of the textile industry in Europe. Currently, the city faces major challenges, including a dramatic population decrease, population ageing as well as a vast revitalisation of urban structures aimed at reinforcing the new idea of the city’s inward development. The research on the layout of Łódź is based on the modern image of the city as well as four images preserved in historical plans. The subsequent, chronological models are analysed in terms of topological features with the use of space syntax methods. The conducted research made it possible to identify the internal, configurational diversity of the historic urban core of Łódź. A seemingly monotonous, orthogonal urban layout is, from a topological perspective, highly diversified. Due to the actions undertaken in Łódź and aimed at restoring urban structures in the broad sense, the study not only has a cognitive goal, but it also carries a practical context.